The rat catchers' Olympics - Cotterill, Colin (Cotterill, Colin. Dr. Siri Paiboun series., 2017)
"1980: The Democratic People's Republic of Laos is proud to be competing in its first-ever Olympics. Of course, half the world is boycotting the Moscow Summer Olympic Games to protest Russia's recent invasion of Afghanistan, but that has made room for athletes from countries that are usually too small or underfunded to be competitive--countries like Laos. Ex-national coroner of Laos Dr. Siri Paiboun may be retired, but he and his wife, Madame Daeng, would do just about anything to have a chance to visit Moscow, so Siri finagles them the job of medical oversight for the Olympians. Most of the athletes are young and innocent village people who have never worn shoes, never mind imagined anything as marvelous as the Moscow Olympic Village. As the competition heats up, however, Siri begins to suspect that one of the athletes is not who he says he is. Fearing a conspiracy, Siri and his friends investigate, liaising in secret with Inspector Phosy back home in Laos to see if the man might be an assassin. But Siri's progress is derailed when another Lao Olympian is accused of murder. Now in the midst of a murky international incident, Dr. Siri must navigate not one but two paranoid and secretive government machines to make sure justice is done"--